Validation of Malay version of the COVID-19 Burnout Scale - Chin Siang, Ang; Kai Wee, Lee; Siok Ping, Voon; Meng Chuan, Ho (Oman Medical Specialty Board, 2022)
Objective: Malaysia had to implement nationwide lockdowns at various times as a mitigation measure to contain the spread of COVID-19 virus. As a result of the lockdowns, necessary quarantines and social distancing practices were put in place. This affected the economic, social, and political scenes in Malaysia and created prolong uncertainly as well as burnout among many Malaysians. The aim of the present research is to develop and validate the Malay version of the COVID-19 Burnout Scale (M-COVID-19-BS).Method: A three-phase study was conducted among Malaysians. Phase 1 involved forward and backward translations by four professional bilingual translators at two different points. Phase 2 involved 30 participants with the aim to assess the semantic, face, and content validation of the Scale. Phase 3 involved 225 Malaysians who took part in a self-administered online questionnaire comprising the M-COVID-19-BS, Copenhagen Burnout Inventory, World Health Organization Quality of Life Scale (Abbreviated Version), and Fear of COVID-19 Scale. Data analysis was performed using SPSS and IBM AMOS. Results: The statistical analysis revealed that the M-COVID-19-BS demonstrated good internal consistency (Cronbach’s alpha = 0.926) and presented with a unidimensional factor structure. M-COVID-19-BS scores positively correlated with the CBI three subscales, showing evidence of convergent validity. Negative correlation was reported between the M-COVID-19-BS with WHOQOL-BREF and with that, discriminant validity was achieved. Lastly, the M-COVID-19-BS exhibited moderate positive correlations with the FCV-19S, concurrent validity was thus supported. Conclusion: Results demonstrated that M-COVID19 BS is a valid and reliable instrument to assess burnout symptoms related to COVID-19 and as self-care tool to detect burnout symptoms without needing to further exacerbate Malaysia’s healthcare system.